Trace element studies of silicate-rich inclusions in the Guin (UNGR) and Kodaikanal (IIE) iron meteorites - Kurat, Gero (2007)
A devitrified glass inclusion from the Guin (UNGR) iron consists of cryptocrystalline feldspars, pyroxenes, and silica and is rich in SiO2, Al2O3, and Na2O. It contains a rutile grain and is in contact with a large Cl apatite. The latter is very rich in rare earth elements (REEs) (∼80 × CI), which display a flat abundance pattern, except for Eu and Yb, which are underabundant. The devitrified glass is very poor in REEs (<0.1 × CI), except for Eu and Yb, which have positive abundance anomalies. Devitrified glass and CI apatite are out of chemical equilibrium and their complementary REE patterns indicate a genesis via condensation under reducing conditions. Inclusion 1 in the Kodaikanal (IIE) iron consists of glass only, whereas inclusion 2 consists of clinopyroxene, which is partly overgrown by low-Ca pyroxene, and apatite embedded in devitrified glass. All minerals are euhedral or have skeletal habits indicating crystallization from the liquid precursor of the glass. Pyroxenes and the apatite are rich in trace elements, indicating crystallization from a liquid that had 10-50 × CI abundances of REEs and refractory lithophile elements (RLEs). The co-existing glass is poor in REEs (∼0.1-1 × CI) and, consequently, a liquid of such chemical composition cannot have crystallized the phenocrysts. Glasses have variable chemical compositions but are rich in SiO2, Al2O3, Na2O, and K2O as well as in HFSEs, Be, B, and Rb. The REE abundance patterns are mostly flat, except for the glass-only inclusion, which has heavy rare earth elements (HREEs) > light rare earth elements (LREEs) and deficits in Eu and Yb - an ultrarefractory pattern. The genetic models suggested so far cannot explain what is observed and, consequently, we offer a new model for silicate inclusion formation in HE and related irons. Nebular processes and a relationship with E meteorites (Guin) or Ca-Al-rich inclusions (CAls) (Kodaikanal) are indicated. A sequence of condensation (CaS, TiN or refractory pyroxene-rich liquids) and vapor-solid elemental exchange can be identified that took place beginning under reducing and ending at oxidizing conditions (phosphate, rutile formation, alkali and Fe2+ metasomatism, metasomatic loss of REEs from glasses).